The future of print media in the Republic of Serbia in the digital age (media-sociological aspect) - Nedeljković, Marko (Sociološki pregled, 2021)
The constant decline in circulation, audience and print revenue, the development of a new culture of information, with the concurrent strengthening of online media, have led to the point where the transformation of print media has become inevitable. Therefore, in theoretical and professional discussions, the key question is how to respond to all changes and ensure the survival of print media outlets. In order to investigate this issue, a study based on the empirical method and the procedure of non-experimental research was conducted, which included five daily newspaper newsrooms in Serbia. The results show that new journalistic competencies are still present on a small scale in most newsrooms, that they are characterized by traditional work organization, as well as that they do not sufficiently involve new media professionals. These are also three key elements that hinder the transformation of print media and their adaptation to the digital age.